Upaya Peningkatan Potensi Wirausaha Melalui Evaluasi Penyuluhan Pembuatan Bakpia Gurih dari Ikan dan Rumput Laut di SMAN 1 Muara Gembong, Bekasi: Fish and Seaweed-Based Cookie Making Training as an Effort to Increase Entrepreneurial Potential at SMAN 1 Muara Gembong, Bekasi - Alsuhendra, Alsuhendra; Ridawati, Ridawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This activity aims to improve the knowledge and skills of teachers, students, and canteen managers at SMAN 1 Muara Gembong, Bekasi, in processing fish and seaweed into high-value products, as an effort to develop entrepreneurial potential. The products made are savory bakpia filled with fish, tempeh, and seaweed. The activity was conducted as training and interactive discussions on July 30, 2025. The training was well attended by 32 participants who gave a rating of 4.7 for the implementation of the training activities, meaning close to very satisfied. The results of the evaluation of participants' knowledge before (pre-test) and after (post-test) the training showed that the pre-test score was 64.0 and the post-test score was 86.7. This indicates that the training activities successfully increased participants' knowledge, with a significant difference of 22.7 points in scores.